Global, regional, and national burden of chronic kidney disease attributable to high sodium intake from 1990 to 2019 - Liu, Wei; Zhou, Lingyun; Yin, Wenjun; Wang, Jianglin; Zuo, Xiaocong (Frontiers in Nutrition, 2023)
Background: The latest global spatiotemporal patterns of CKD burden attributable to high sodium intake still remain unclear. Methods: Data were extracted from the Global Burden of Disease (GBD) Study 2019. The number of CKD cases and age-standardized mortality rate (ASMR) and disability-adjusted life years rate (ASDR) were estimated by age, sex, SDI, region, and country. The estimated annual percentage change (EAPC) was calculated to evaluate the secular trends of ASMR and ASDR. We further explored the associations of SDI with the ASMR and ASDR of CKD attributable to high sodium intake. Results: Globally, the death number and disability-adjusted life years (DALYs) of CKD attributable to high sodium intake were 45,530 (95% UI: 12,640 to 93,830 ) and 1.32 million (95% UI: 0.43 to 2.8) in 2019, both twice as many as those in 1990. However, the ASMR and ASDR slightly grew, with an EAPC of 0.22 (95% CI: 0.16 to 0.28) and 0.10 (95% CI: 0.04 to 0.16), respectively. The age-specific numbers and rates of deaths, as well as DALYs of CKD attributable to high sodium intake rose with age and were greater in males than in females. The rate of death and DALY peaked at the >95 age group for females and males in 2019. The rate of age-specific CKD death and DALY attributable to high sodium intake decreased in patients aged under 55-59 and increased in those aged above 59. The burden of CKD attributable to high sodium intake in 2019 and its temporal trends from 1990 to 2019 varied greatly by SDI quintile and geographic location. The ASMR or ASDR showed a non-linear negative correlation with SDI at the regional level. The EAPC in ASMR or ASDR represented a negatively correlation with ASMR or ASDR in 1990, with a coefficient of 0.40. Nevertheless, the EAPC in ASMR not in ASDR was positively correlated with SDI in 2019, with a coefficient of 0.18. Conclusion: Strengthened and tailored approaches for CKD prevention and sodium intake management are still needed to reduce the CKD burden associated with high sodium intake, especially for elderly populations, males, and regions with middle SDI.